Effect of hypervitaminosis A on the histological structure of liver in albino rat - Nawraa Abdul Sattar Al-awsi; Dr. Ali Fayadh Bargooth (International Journal of Medical Toxicology and Legal Medicine, 2024)
The importance of vitamin A as it is important for normal vision, the immune system, reproduction, growth and development. The aim of the experiment is to study the histological effects in liver from the hypervitaminosis A .Forty adult male Wistar rats were divided into four groups randomly that were given vitamin A orally For sixty days, 10 rats in the control group received distilled deionized water every day. Three experimental groups received varying doses of vitamin A. IU daily for 60 days: low dose (LD, 10 mice) (8000 IU/mouse/day), intermediate dose (ID, 10 mice, 12000 IU/mouse/day), and high dose (HD, 10 mice, 15000 IU/mouse/day). The LD groups appeared less of histological changes in liver, but the livers in the ID and HD groups showed deeply histological changes with classification and fibrosis . In conclusion, the histopathology of the liver was affected by increasing vitamin A dose with the appeared of calcification and fibrosis